A Compact Chemical Kinetic Mechanism for Heavy Fuel Surrogates with n‑, iso- and cyclo-Alkanes, and Aromatic Compounds - Zettervall, Niklas; Nilsson, Elna J. K. (ACS omega, 2025)
Modeling of real-world fuels and fuel mixtures in combustion engines, using computational fluid dynamics (CFD), calls for the development of compact and computationally efficient chemical kinetic mechanisms. To improve the modeling capabilities of multicomponent fuels it is necessary to transition from the single-component descriptions of fuels and move toward more complex, accurate multicomponent ones, where different functionality groups are included. In this work a newly developed multicomponent reaction mechanism, capable of modeling the four different functionality groups n-, iso-, cyclo-alkanes and aromatics, is presented. The mechanism consists of seven fuel components with different molecular sizes and the mechanism offers the possibility to create surrogate fuels for real-world fossil and alternative fuels and fuel mixtures. The presented mechanism accurately models key combustion parameters at a wide range of conditions, considering the intrinsic characteristics of the four functional groups. The presented mechanism offers a unique combination of fuel flexibility, modeling performance and a low computational cost, and it opens up the possibilities to cost-efficient CFD simulations of multicomponent surrogate aviation fuels.